2007
DOI: 10.1002/gps.1747
|View full text |Cite
|
Sign up to set email alerts
|

Instrumental activities of daily living in the screening of dementia in population studies: a systematic review and meta‐analysis

Abstract: The functional assessment of the IADL showed an acceptable efficiency for the screening of dementia in the population studies included in this review, although few studies have verified this efficiency (sensitivity and specificity of the scales used). Further research is necessary in this field to be able to draw definitive conclusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
35
0
3

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 21 publications
4
35
0
3
Order By: Relevance
“…81 IADL scales have been shown to be 'reliable, sensitive and responsive' and useful in dementia screening in a heterogeneous Indian population 83 , with acceptable efficiency for dementia screening. 84 They have been shown to compare favourably against the MMSE when administered by General Practitioners and have the advantage of being simple and nonthreatening to administer. 85 It has been shown that subjects who performed poorly on ?…”
Section: African Journal Of Psychiatry • November 2013mentioning
confidence: 99%
“…81 IADL scales have been shown to be 'reliable, sensitive and responsive' and useful in dementia screening in a heterogeneous Indian population 83 , with acceptable efficiency for dementia screening. 84 They have been shown to compare favourably against the MMSE when administered by General Practitioners and have the advantage of being simple and nonthreatening to administer. 85 It has been shown that subjects who performed poorly on ?…”
Section: African Journal Of Psychiatry • November 2013mentioning
confidence: 99%
“…The use of standardized scales assessing IADL in elderly persons experiencing cognitive impairment may be useful in addition to commonly used cognitive tests for an earlier, more accurate diagnosis of MCI and prediction of dementia [1]. There is a large variability in measuring IADL and more research is needed regarding the relationship between IADL and cognitive processes [12,13]. …”
Section: Introductionmentioning
confidence: 99%
“…We enjoyed reading the systematic review and meta-analysis of Castilla-Rilo et al (2007) concerning IADL in the screening for dementia in population studies. This is an interesting topic because an IADL scale might be a short and simple screening instrument for dementia.…”
mentioning
confidence: 99%
“…BADL contains basic self-maintenance skills and IADL more complex activities of daily living (Lawton and Brody, 1969). In the article of Castilla-Rilo et al (2007) the terms 'functional assessment' and 'IADL' are used interchangeable, while they are in fact separate terms. Moreover, no clear distinction was made between scales measuring exclusively IADL and scales measuring functional status.…”
mentioning
confidence: 99%